Zero Energy Overwinter Storage of Apple Nursery Plants in trans-Himalayan Ladakh, India - Angmo, Phunchok; Chandel, Joginder S; Katiyar, Anand Kumar; Targais, Konchok; Chaurasia, O P; Stobdan, Tsering (Defence Life Science Journal, 2018)
Studies were conducted during 2015 and 2016 to assess the effects of storage conditions on survival of nursery plants in trans-Himalayan Ladakh region. Apple nursery plants raised under warm climatic conditions of Solan (Himachal) were lifted from nurseries in first week of January and stored upto March in cold Ladakh region. Underground cellar-stored plants showed significantly higher plant survival (92 to 94%) than greenhouse-stored plants (37 to 56% survival). Low and constant temperature (-1.5±4.1 to 10.0±1.4ºC) and absence of light inside the cellar were favorable factors for storage of nursery plants. Lower survival rates of greenhouse-stored plants could be attributed to lower and greater fluctuations in temperature (-9.3±1.7to 25.1±1.9ºC) inside the greenhouse. Cellar-stored plants were less subjected to freezing injury as reflected from shoot electrolyte leakage studies. The underground cellar was found effective for overwinter storage of apple nursery plants for 3 to 4 months. The method described is easy and cost-effective, and can be a satisfactory alternative to refrigerated cold storage in trans-Himalayan region with severe winters.